The Iranian expanse: transforming royal identity through architecture, landscape, and the built environment, 550 BCE-642 CE - Canepa, Matthew P. (The Joan Palevsky imprint in classical literature, 2018)
"The Iranian Expanse explores how kings in the ancient Iranian world utilized the built and natural environment--everything from royal cities and paradise gardens, to hunting enclosures and fire temples--to form and contest Iranian cultural memory, royal identity, and sacred cosmologies over a thousand years of history. Although scholars have often noted startling continuities between the traditions of the Achaemenids and the art and architecture of medieval or Early Modern Islam, the tumultuous millennium between Alexander and Islam has routinely been downplayed or omitted. The Iranian Expanse delves into this fascinating period, examining royal culture and identity as something built and shaped by strategic changes to architectonic and urban spaces and the landscape of Western Asia. Canepa shows how the Seleucids, Arsacids, and Sasanians played a transformative role in developing a new Iranian royal culture that deeply influenced not only early Islam, but also the wider Persianate world of the Il-Khans, Safavids, Timurids, and Mughals."--Provided by publisher